1998
DOI: 10.1159/000014999
|View full text |Cite
|
Sign up to set email alerts
|

Detailed genetic mapping around a putative prostate-specific membrane antigen locus on human chromosome 11p11.2

Abstract: Physical mapping of the human prostate-specific membrane antigen gene (FOLH) has not been straightforward. Previously, localisations of this gene to either 11p11.2 or 11q14 have been described. This raised the possibility of the presence of more than one related FOLH gene in man. We now present detailed characterisation of the region around a FOLH gene in a 500-kb non-chimaeric YAC clone, putatively assigned to 11p11.2. This clone contains two known microsatellites, D11S1326 and D11S1357 which have been previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…More recently, this 11p localisation has been confirmed [10]. Further investigations have also revealed that these interesting PSM loci on 11p11.2 and 11q14 are duplicated over a region of at least 500 kb [9]. …”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…More recently, this 11p localisation has been confirmed [10]. Further investigations have also revealed that these interesting PSM loci on 11p11.2 and 11q14 are duplicated over a region of at least 500 kb [9]. …”
Section: Introductionmentioning
confidence: 69%
“…This was in contrast to the findings by Rinker–Schaeffer et al [8]who only detected a single 11q14 PSM fluorescent in situ hybridisation (FISH) signal at high stringency and therefore suggested the long arm as being the true location of the known PSM gene. On balance, the 11p11.2 region is now thought to be the more likely location of the known human PSM gene as evidenced by sequencing and detailed genetic mapping studies [9]. More recently, this 11p localisation has been confirmed [10].…”
Section: Introductionmentioning
confidence: 99%
“…25 These studies also suggest extensive genetic duplication in these two regions (11p11.2 and 11q14). This phenomenon is observed elsewhere in the human genome and usually some members of the resulting gene families eventually lose function and become pseudogenes.…”
Section: Mapping Of the Psm/folh1 Genementioning
confidence: 85%
“…However, this has now been resolved. 25,52 Detailed genetic analysis has allowed localisation of the FOLH1 gene to the 1lp11.2 chromosomal region at 62.5 cM, with a related FOLH2 gene at 11q14. Interestingly there appears to be extensive genetic duplication, over at least 500 kb, in these two regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation